A fluorimetry-based ssYFP secretion assay to monitor vasopressin-induced exocytosis in LLC-PK(1) cells expressing aquaporin-2 - Nunes, Paula (American Physiological Society, 2008)
Vasopressin (VP)-induced exocytosis was dissected in native and aquaporin-2 (AQP2)-expressing renal LLC-PK(1) cells by a fluorimetric exocytosis assay based on soluble secreted yellow fluorescent protein (ssYFP). YFP was targeted to the secretory pathway by addition of an 18-amino acid signal peptide from hen egg white lysozyme. Immunofluorescence labeling, together with analysis of Alexa 555-dextran internalization, revealed that ssYFP is exclusively located in the secretory pathway. Immunofluorescence and immunogold electron microscopy showed significant colocalization of ssYFP and AQP2. Fluorimetry and Western blot analysis demonstrated similar constitutive ssYFP secretion in native LLC-PK(1) and AQP2-expressing cells. In AQP2-expressing cells, a twofold increase in ssYFP secretion was observed within 15 min of VP stimulation. This transient burst of ssYFP secretion was abolished by the PKA inhibitor H-89 and was not observed in native cells. The endocytotic inhibitor methyl-β-cyclodextrin, which also promotes membrane accumulation of AQP2, had no effect on ssYFP secretion. Although cells expressing phosphorylation-deficient AQP2-S256A showed significantly lower baseline levels of constitutive secretion, VP induced a significant increase in exocytosis. Our data indicate that 1) this assay can monitor exocytosis in cultured epithelial cells, 2) VP has an acute stimulatory effect on ssYFP secretion in AQP2-expressing, but not native, cells, and 3) phosphorylation of AQP2 at S256 may be involved in the regulation of constitutive AQP2 exocytosis and play only a minor role in the VP-induced burst. These results support the idea that, in addition to its role in reducing AQP2 endocytosis, VP increases AQP2 exocytosis.